THE PARTICIPATORY THAI ART EXHIBITION MODEL TO PROMOTE THE APPLICATION OF THAI ART IN DAILY LIFE FOR YOUTH - Charangsri, Wanalee; Pholprasert, Apichart (Journal of Social Science and Cultural, 2023)
This research aimed to Develop the participatory Thai art exhibition model to encourage the use of Thai art in daily life. This research is Research and Development technique. There are 2 sample groups: The first group is used to study information to develop a participatory Thai art exhibition. These sample group are experts has been selected with purposive sampling method. Data were collected through interviews and observations of Thai art activities and participatory exhibitions. The second group was used to experiment with a participatory Thai art exhibition model, including 53 of 18 - 25 years old youths who visited the exhibition with and participated in the creative activities. 32 Participants were selected by voluntary selection. The tools used to collect data included commentary surveys on learning spaces of participatory Thai art exhibition, feedback surveys on creative Thai art activities in daily life, evaluation of the ability to apply Thai art. Data Analysis using mathematical averages, standard differences, and data analysis. The results of the research were a formation of a model for a participatory Thai art exhibition to promote the daily application of Thai art for young people. This research has developed the exhibition principles by using the learning management method according to the 4 MAT learning cycles. The exhibition consists of 2 parts: 1) is a learning area for participatory Thai art exhibitions. and 2) is the space for creative Thai art activities. The results of a participatory art exhibition experiment showed that young people had the highest level of opinion and satisfaction about the exhibition ( = 4.86, SD = 0.28). Young people had their highest levels of opinion, satisfaction with the art activities ( = 4.83, SD = 0.15). The evaluation of the work from the application of Thai art found that the average youth’s application of Thai art scores was very good, ( = 13, SD = 0.29)